Salinity stress simulation on Acehnese local rice (Oryza sativa L.) with NaCl in the method of in vitro germination - . Efendi; Elly Kesumawati; Sabaruddin Zakaria; . Syafruddin; . Syamsuddin; . Hasanuddin (Syiah Kuala University, 2013)
Agricultural yield was negatively impacted by salt stress throughout around the world affecting production whether it is for economic gain or subsistence. The tolerance of Acehnese local rice on salinity stress was studied with using osmotic condition in the method of in vitro germination. NaCl was applied on medium MS for the salinity stress simulation for studying the capability of the various osmotic conditions in selection of some Acehnese local rice for the tolerance of salinity stress. The objective of this research was to simulate with in vitro method the tolerance of some varieties of Acehnese local rice on salinity stress during seed germination. Sixteen varieties of Acehnese local rice was sterilized and germinated in vitro for tens days in 250 ml bottle containing 25 ml of medium MS with applying NaCl as concentration 0, 0.5, 1.0, 1.5 and 2.0 g/liter. The varieties of Acehnese local rice that used in this research are Ciherang as control variety, and Acong, Padi Mas, Aweuh, Rom Mokot, Bo Santeut, Sigudang, Bo 100, Sanbei, Sigupai, Manggeng, Sipirok, Padi Berselona, Salah Mayang Ru, Pandrah, dan Sikuneng. The results of this study showed that the tolerance of Acehnese local rice different significantly on observed viability of the seeds: seed growth rate, germination capacity, growth velocity, growth unity, and seedling fresh weight. The osmotic condition of NaCl resulted an effective method to simulate the tolerance of salinity stress for Acehnese local rice using NaCl in the method of in vitro cultivation. The solution with 2.0 g/l of NaCl that used to study the responds of Acehnese local rice to the tolerance of salinity stress was obtained as the best concentration. Thus, simulation of salinity stress condition on Acehnese local rice will become an alternative method for selection of genotype traits related to the tolerance of salinity stress for local rice in the future